Evaluation model of information technology innovation effectiveness : Case of higher education institutions in Indonesia - Qomarul Huda, Muhammad; Hussin, Husnayati (2017)
Information Technology (IT) innovation implementation in an organization seems to be more challenging than expected. IT innovation adoption is relatively controllable, while the investigating way of work of IT implementation is far more difficult to control as it involves complex interactions among individuals, technology, and the environment. Similar to other organizations, higher educational institutions are also involved in IT innovation implementation. IT innovation is seen as key enabler to transform higher education, nevertheless many IT implementation initiatives are far from successful. This study proposed an IT innovation effectiveness model for higher education and investigates what are the factors that contribute to IT innovation effectiveness. The proposed model was based on the post adoption stage of Diffusion of Innovation theory and Klein and Sorra’s innovation implementation model. The model was adapted to the higher education context by including new variables. Using the survey method, the model was validated using a sample of 91 higher educational institutions in Indonesia. The findings of the study confirmed that top management support (TMS) influence successful IT innovation effectiveness (ITNE) both directly and indirectly through implementation policies and practices (IPP) of ITNE. Consequently, top management bodies in the context of the HEIs in Indonesia should prioritize on IPP first. This will enable implementation policies to influence on successful ITNE. In a similar manner, the role of IPP is very important as mediator of the relationship between TMS and ITNE to achieve success of ITNE.